2019
DOI: 10.1136/bmjgh-2019-001613
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal antibody responses to a live oral poliovirus vaccine challenge among adults previously immunized with inactivated polio vaccine in Sweden

Abstract: BackgroundOur understanding of the acquisition of intestinal mucosal immunity and the control of poliovirus replication and transmission in later life is still emerging.MethodsAs part of a 2011 randomised, blinded, placebo-controlled clinical trial of the experimental antiviral agent pocapavir (EudraCT 2011-004804-38), Swedish adults, aged 18–50 years, who had previously received four doses of inactivated polio vaccine (IPV) in childhood were challenged with a single dose of monovalent oral polio vaccine type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The possibility that induction of mucosal immunity to poliovirus is less robust after infancy is further supported by recent findings from a study of Swedish adults, who had received IPV in childhood as part of routine immunization programs 54 , 55 (Fig. 1 ).…”
Section: Mucosal Immunity In Older Children and Adultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The possibility that induction of mucosal immunity to poliovirus is less robust after infancy is further supported by recent findings from a study of Swedish adults, who had received IPV in childhood as part of routine immunization programs 54 , 55 (Fig. 1 ).…”
Section: Mucosal Immunity In Older Children and Adultsmentioning
confidence: 65%
“… Clinical trials were conducted to assess induction of polio type-specific immunity in response to immunization and OPV challenge in infants (FIDEC, Chile, Panama) 11 13 , children (Lithuania) 51 , and adults (Sweden, Belgium) 54 , 56 . Induction of polio type-specific intestinal immunity for each trial was evaluated in a related set of studies 16 18 , 51 , 55 , 57 . Details of the primary immunization schedules and type-specific OPV challenges for each study are published and briefly summarized here.…”
Section: Mucosal Immunity To Live and Inactivated Poliovirus Vaccines In Infantsmentioning
confidence: 99%
“…In the current study, as in others, there was a strong correlation between intestinal poliovirus-specific IgA and neutralization. A study in young Swedish adults who had received IPV in infancy and were challenged with oral monovalent polio type 1 found that they had an even more limited intestinal immune response [ 23 ]. The immunologic mechanisms underlying this immune blockade are under active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Such models require careful ethical consideration, as well as selection, validation, and testing of a proper challenge agent that can reliably cause infection at a predictable attack rate in susceptible individuals without risk of significant disease. CHIMs are often not ethical to perform in children, but use of approved oral vaccines as challenge agents, as have been used extensively in the poliovirus field 5 10 , shows promise but remains underexplored in the evaluation of mucosal immunity to RVA and rotavirus CoPs.…”
Section: Introductionmentioning
confidence: 99%